2012
DOI: 10.1038/nature11528
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes to the Gulf Stream causing widespread gas hydrate destabilization

Abstract: The Gulf Stream is an ocean current that modulates climate in the Northern Hemisphere by transporting warm waters from the Gulf of Mexico into the North Atlantic and Arctic oceans. A changing Gulf Stream has the potential to thaw and convert hundreds of gigatonnes of frozen methane hydrate trapped below the sea floor into methane gas, increasing the risk of slope failure and methane release. How the Gulf Stream changes with time and what effect these changes have on methane hydrate stability is unclear. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(136 citation statements)
references
References 26 publications
2
133
0
1
Order By: Relevance
“…Apart from the Arctic, hydrate deposits in relatively shallow waters (300-700 m) in the Gulf of Mexico or along the western North Atlantic Margin will, most likely, be affected by global warming as well [Reagan and Moridis, 2007;Phrampus and Hornbach, 2012;Skarke et al, 2014]. In addition, variations in the location of ocean currents and an additional warming on decadal time scales might lead to the local dissociation of marine gas hydrates.…”
Section: Compared Tomentioning
confidence: 99%
“…Apart from the Arctic, hydrate deposits in relatively shallow waters (300-700 m) in the Gulf of Mexico or along the western North Atlantic Margin will, most likely, be affected by global warming as well [Reagan and Moridis, 2007;Phrampus and Hornbach, 2012;Skarke et al, 2014]. In addition, variations in the location of ocean currents and an additional warming on decadal time scales might lead to the local dissociation of marine gas hydrates.…”
Section: Compared Tomentioning
confidence: 99%
“…Model outputs suggest that bathyal areas particularly prone to declining POC flux lie in the Norwegian and Caribbean Seas, NW and NE Atlantic, the eastern tropical Pacific, and bathyal Indian and Southern Oceans, which could experience as much as a 55% decline in POC flux by 2100 (Tables 2, 3; Figures 2, 3). Elevated seafloor temperatures at northerly latitudes (Figure 2) will lead to warming boundary currents and may trigger massive release of methane from gas hydrates buried on margins (Phrampus and Hornbach, 2012;Johnson et al, 2015) especially in the Arctic, with simultaneous effects on global climate, aerobic methane oxidation, water column de-oxygenation and ocean acidification (Biastoch et al, 2011;Boetius and Wenzhöfer, 2013). Along canyon-cut margins (e.g., the western Mediterranean), warming may additionally reduce density-driven cascading events, leading to decreased organic matter transport to the seafloor (Canals et al, 2006), though this very process is also likely to reduce physical disturbance at the seafloor.…”
Section: Seafloor Ecosystem Changes Under Future Climate Change Scenamentioning
confidence: 99%
“…It has been reported that methane is produced not only in anaerobic environments but also in aerobic environments such as the water at the surface of the ocean, possibly through the decomposition of methylphosphonate (Karl et al 2008) or via methanogenesis (Grossart et al, 2011). On the seafloor, destabilization of methane hydrate due to changes in ocean temperature has been found to occur in the North American margin (Phrampus & Hornbach, 2012), possibly releasing methane into the water column. Marine hydrothermal systems distributed widely along mid-ocean ridges and back-arc basins (Van Dover, 2011) are another source of methane in the ocean (Takai & Nakamura, 2010).…”
mentioning
confidence: 99%